Acetyl-cholinesterase enzyme inhibitory effect of calophyllum species - Cheng, Gwendoline Lian Ee; Soek, Sin Teh; Siau, Hui Mah; Jamaluddin, Nur Ain; Muhamad Sahimi, Muhamad Syarik; Ahmad, Zuraini (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2015)
Purpose: To search for new acetylcholinesterase enzyme inhibitors from Calopyllum species.